Analysis Of Critical Thinking Skill Level Of Students Smp Negeri 2 Padang about Environmental Pollution - Novia Daniati; Dezi Handayani; Relsas Yogica; Heffi Alberida (ATRIUM PENDIDIKAN BIOLOGI, 2018)
Curriculum of 2013 requires students to be able to think critically. This critical thinking ability can be trained by using questions that have indicators of critical thinking, besides those questions must also have cognitive levels C4 (analyze), C5 (evaluate), and C6 (synthesize). Padang Public Middle School 2 has implemented 2013 Curriculum in learning, but students' critical thinking skills are unknown. This research is a descriptive research. The method used in this research is descriptive method. The subject of the study consisted of 48 students of class VII of SMP Negeri 2 Padang. The data obtained in this study was obtained through test techniques. The test used is a description test. The test instruments used will be validated and analyzed first. Analysis of this instrument includes the level of difficulty, differentiation and reliability. Test instruments were tested before being used. This study produces data that the level of critical thinking skills of seventh grade students in Padang State Middle School is still in non-critical qualifications with a percentage average value of 48.53%. Indicators with the highest average percentage to the lowest, namely; the inference indicator obtained a score of 69.96% with quite critical qualifications; the indicator gives a basic statement obtained a value of 60.62% with less critical qualifications; the indicator estimates that a value of 53.12% is obtained with non-critical qualifications; the indicator gives an advanced statement obtained a value of 44.39% with non-critical qualifications, and; basic indicators of decision making obtained a value of 14.58% with non-critical qualifications. Keywords: Critical Thinking, Environmental Pollution, Descriptif